Recurso de apelación en el proceso verbal inmediato. Autoridad competente para resolverlo: riesgo de impedimento o recusación (2021)
This article analyzes an error, clearly illegal, that is being committed by police authorities, academics, scholars and litigants, in this area of Law, by accepting, tacitly or expressly, that police inspectors and “corregidores” are competent to resolve the appeal against corrective measures imposed by uniformed members of the National Police, designated as commanders of station, substations or Immediate Attention Centers. The analysis evidences that this authority does not belong to the police inspector or corregidor, in accordance with the constitutional precepts, the jurisprudence of the Constitutional Court and the Council of State and Law 1801 of 2016. Furthermore, it is shown that if the appeal against police decisions made by the former commanders is resolved by the inspector or corregidor, they could also be the subject to criminal and disciplinary investigation, or it could result in the declaration of nullity of the act by the Contentious Administrative Jurisdiction.